Emerging Technologies and Marketing Strategy: A Bibliometric Review of Digital Marketing and Innovation - Legito, Legito; Eva Andriani (The Eastasouth Journal of Information System and Computer Science, 2023)
The landscape of marketing strategies is undergoing a profound transformation fueled by the rapid emergence of technologies. This study employs a comprehensive bibliometric analysis to explore the dynamic relationship between emerging technologies, marketing strategies, digital marketing, and innovation. Through co-citation analysis, bibliographic coupling, keyword co-occurrence analysis, and VOSviewer visualizations, the research objectives are achieved, unraveling trends, influential authors, institutions, and research themes within the multidimensional field. Findings underscore the multidisciplinary nature of the domain, highlighting clusters ranging from customer satisfaction and digital platforms to market orientation and social media marketing. Prominent keywords like "Social Medium," "Performance," and "Digital Transformation" reveal the industry's focus on platforms, effectiveness assessment, and adaptability. Keywords with fewer occurrences, such as "Product Innovation" and "Artificial Intelligence," pinpoint specialized areas of exploration. The study contributes a holistic understanding of the evolving relationship between emerging technologies and marketing strategies, informing future research directions and guiding innovative practices in the digital era.